2014
DOI: 10.1038/cddis.2014.473
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction-associated OPA1 cleavage contributes to muscle degeneration: preventative effect of hydroxytyrosol acetate

H Li2,
et al.

Abstract: Mitochondrial dysfunction contributes to the development of muscle disorders, including muscle wasting, muscle atrophy and degeneration. Despite the knowledge that oxidative stress closely interacts with mitochondrial dysfunction, the detailed mechanisms remain obscure. In this study, tert-butylhydroperoxide (t-BHP) was used to induce oxidative stress on differentiated C2C12 myotubes. t-BHP induced significant mitochondrial dysfunction in a time-dependent manner, accompanied by decreased myosin heavy chain (My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 47 publications
(59 reference statements)
5
58
0
Order By: Relevance
“…Cells were induced into myotubes after 6 days following previously reported method [27]. siRNA transfections were performed using Lipofectamine RNAiMAX (Invitrogen), and DNA transfections were performed using X-tremeGENE HP DNA transfection reagent (Roche, Basel, Switzerland) as described in the supplier's manuals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were induced into myotubes after 6 days following previously reported method [27]. siRNA transfections were performed using Lipofectamine RNAiMAX (Invitrogen), and DNA transfections were performed using X-tremeGENE HP DNA transfection reagent (Roche, Basel, Switzerland) as described in the supplier's manuals.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial complex activity assays Mitochondria isolation from cultured mouse C2C12 myoblasts, myotubes and skeletal muscle tissues were performed as previously described [27,28]. Mitochondrial complex activities were measured by spectrophotometer as described in previous reports [29,30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies demonstrated that mitochondrial dysfunction precedes and activates muscle atrophy signaling in Dex-induced muscle atrophy models [12] and some natural plant extracts, including hydroxytyrosol acetate, resveratrol and quercetin, can target the mitochondria to improve mitochondrial function and prevent muscle atrophy under several wasting conditions [12][13][14]. Thus, development of drugs or nutrients that improve mitochondrial function could be beneficial in preventing Dex-induced muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…10 mM antimycin A, 6 mM carbonyl cyanide-p trifluoromethoxyphenylhydrazone (FCCP), and 10 mM oligomycin were used as inhibitors, and the basal, maximal, ATP-linked and proton leakage, were determined and adjusted by protein concentration (32).…”
Section: Protein Carbonylation Assaymentioning
confidence: 99%